2015
DOI: 10.1590/s1806-92902015001000001
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of fish meal by protein soybean concentrate in practical diets for Pacific white shrimp

Abstract: -The objective of this work was to evaluate the performance of Litopenaeus vannamei fed different levels (0, 25, 50, 75, and 100%) of soybean protein concentrate (63.07% crude protein, CP) to replace fish meal-by product (61.24% CP). The study was conducted in clear water in fifteen 800 L tanks equipped with aeration systems, constant heating (29 ºC), and daily water exchange (30%). Each tank was stocked with 37.5 shrimp/m 3 (3.03±0.14 g). Feed was supplied four times a day, at 6% of the initial biomass, adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 25 publications
3
11
0
Order By: Relevance
“…Incurring the negative effects of higher inclusion levels of SPC in the diet of L. vannamei , Sookying () observed a significantly lower weight gain and higher FCR in shrimps fed with diets containing SPC at 20% or greater and suggested a possibility of limited (10%) inclusion of SPC replacing SESBM without compromising the growth. Furthermore, Soares et al, () reported a negative linear trend for total weight gain and feed intake as replacement of fishmeal by SPC. However, replacing up to 75% of fish meal by SPC (27% inclusion) did not significantly impaired the growth of shrimp (Soares et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Incurring the negative effects of higher inclusion levels of SPC in the diet of L. vannamei , Sookying () observed a significantly lower weight gain and higher FCR in shrimps fed with diets containing SPC at 20% or greater and suggested a possibility of limited (10%) inclusion of SPC replacing SESBM without compromising the growth. Furthermore, Soares et al, () reported a negative linear trend for total weight gain and feed intake as replacement of fishmeal by SPC. However, replacing up to 75% of fish meal by SPC (27% inclusion) did not significantly impaired the growth of shrimp (Soares et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Soares et al, () reported a negative linear trend for total weight gain and feed intake as replacement of fishmeal by SPC. However, replacing up to 75% of fish meal by SPC (27% inclusion) did not significantly impaired the growth of shrimp (Soares et al, ). In contrast, Bauer, Prentice‐Hernandez, Tesser, Wasielesky, and Poersch () revealed the possibility of complete replacement of fish meal with SPC (up to 28% as is) without causing significant differences in weight gain and FCR of L. vannamei fed with diets supplemented with DL‐Methionine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A linear trend was found for final weight, weekly weight gain, total weight gain, and feed intake as replacement of FM by SPC increased. This implied that 75% FM replaced by SPC did not affect shrimp growth Soares et al [56]. Biswas [57], reported that replacement of fishmeal with SPC at up to 70% without amino acid supplementation and attractant improves growth performance and digestibility in fish.…”
Section: Effects Of Spc On Growth Performance In Fish and Crustaceansmentioning
confidence: 97%
“…Zhou et al (2015) tested eight diets formulated mainly with soybean meal and only 6% of fish ingredients without significant difference with respect to shrimp perfomance. Soares et al (2015) used diets with different level (0, 25, 50, 75, and 100%) of soybean protein concentrate, indicating that fishmeal can be replaced with 75% of soybean protein concentrate without negatively affecting the shrimp performance. Chen et al (2017) suggested that a 25% of fishmeal can be replaced by soy protein concentrate; while Van Nguyen et al (2017) suggested the same percentage but by fermented soybean meal without adverse effects on growth and feed utilisation of shrimp.…”
Section: Introductionmentioning
confidence: 99%